Financial distress prediction with knock out real options: a study for the argentine market - Milanesi, Gastón Silverio (Estudios de Administración, 2019)
This paper explores default prediction models based on real options theory, proposing a simple model using exotic barrier options. Financial distress prediction models consider the value of net capital as if it were a call option over the firm’s assets. Its main weakness resides in the direct relationship between an asset’s volatility and its option value.For certain critical levels of assets, the knock-out barrier option type inversely adjusts the relationship between volatility and net capital value. Along this line, a naive version of barrier models is proposed for predicting financial distress and calculating default values for firms, sector and the market. First, a case method is employed to make a comparative analysis between the traditional naive model and the naive barrier options. The sensitivity analysis is applied over variables such as volatility, leverage and time horizon, and is implemented over a representative sample of Argentinian market firms. The results obtained indicated that the barrier option model developed better. With increased volatility, net capital value tended to decline, and showed direct correlation between volatility and default probabilities. The model is a useful tool to predict firms’ probabilities and risk of default, at the individual or aggregated level.